Effects of flipped classroom towards calculus performance and mathematical creative thinking skills among higher institution students - Mohd Ayub, Ahmad Fauzi; Razali, Fazilah; Ghazali, Norliza (Springer New York, 2024)
This study aimed at determining the effect of flipped classroom approach on mathematics achievement and interest of students. Given this, a quasi-experimental design was used, specifically non-equivalent pretest-posttest control group design. The study’s population comprised six hundred and seventy-three seniors in class one (SS 1) from Igbo-Etiti Local Government Area in Enugu State. The study’s participants were a sample of 86 learners selected from two schools purposively. Each school had two SS 1 classes, divided into experimental and control groups via balloting. Data were gathered through the instrumentality of the Mathematics Achievement Test (MAT) and Mathematics Interest Inventory (MII), which have reliability scores of 0.88 and 0.79, respectively. Prior to and following a six-week course of treatment, each group completed a pretest and posttest. SPSS, a statistical tool for social sciences, was applied to analyse the acquired data. The mean and standard deviation were utilised to report the study’s questions, and analysis of covariance (ANCOVA) was utilised to evaluate the hypotheses at a 0.05 significance level. Results established that learners taught mathematics utilising flipped classroom approach had higher mathematics achievement and interest scores than their peers taught using the conventional approach. Results also revealed that the achievement and interest scores of male and female learners who received mathematics instruction using flipped classroom approach were the same. Considering the findings, recommendations were given, among others, that mathematics teachers should use the flipped classroom approach to assist learners in boosting their achievement and interest in mathematics, especially in geometry.